Applications of Capacitance in Monitoring of Microbial Biofilms - Singh, Pawandeep (My University, 2014)
Biofilm is an assemblage of microbial cells that is irreversibly associated with a surface and usually enclosed in a matrix of polysaccharide material. Current methods i.e. Fibre optical sensors, Photoacoustic Spectroscopy etc. are used for biofilm monitoring but they are used to monitor thin biofilms. Present study was conducted to develop non-invasive method for measuring biofilm. For this sensor was fabricated using capacitance based methods. Four isolates out of twenty five were screened on the basis of their biofilm forming capability. Architectural differences between EPS and biofilm of each isolate was analysed using Scanning Electron Microscope. Biochemical characterization confirmed the presence of charged functional groups such as sugars, proteins and amino sugars. For analysing biofilm age and EPS concentration, aluminium matrix was used as appropriate conducting material. It was observed that maximum capacitance was measured for EPS BP19 at 6 mg/ml followed by BP10 at 5 mg/ml and BP7 and BP4 at 4 mg/ml concentration. Highest capacitance of 53854pF was observed for BP4 at the time of 72 hours and lowest was observed in case of BP10 of 37894pF. In conclusion we anticipate the developed sensor could be used for in situ biofilm analysis.
MS, DBTS
Keywords: parallel plate capacitor; biofilm measurement; Capacitance; Biopolymer